Carrier Injection and Annealing‐Enhanced Electrical Performance in Tunnel Oxide‐Passivated Contact Silicon Solar Cells. Issue 1 (17th November 2021) - Hu, Zechen; Song, Lihui; Lin, Dehang; He, Qiyuan; Zhang, Xiujuan; Cai, Yongmei; Fang, Lingxin; He, Sheng; Hsu, WeiChih; Yu, Xuegong; Yang, Deren
Abstract : Herein, it is demonstrated that low temperature current injection and annealing (CIA) treatment can cause evident improvements in open circuit voltage, short‐circuit current, and fill factor of tunnel oxide‐passivated contact (TOPCon) silicon solar cells, leading to a notable conversion efficiency gain (over 0.4% absolute at the best condition). The effects of injected current and annealing temperatures toward the improvement of electrical performance of the TOPCon solar cells are compared. The more evident increase in the electrical performance after the CIA treatment may come from the higher fill factor improvements, which can be induced by the change of contact resistance after the CIA treatment, the potential involvement of hydrogen is discussed. The CIA treatment can be a reliable approach to further enhance the conversion efficiency of TOPCon solar cells, which is of great significance for the global PV industry. Abstract : Herein, is been demonstrated that low temperature current injection and annealing can cause evident improvements in the conversion efficiency (over 0.4% absolute at the best condition) of tunnel oxide‐passivated contact silicon solar cells. Furthermore, the effects of injected current and annealing temperatures toward the electrical performance enhancement are compared and discussed.